ANALISIS PERILAKU KONSUMEN DALAM MELAKUKAN ONLINE SHOPPING DI KOTA DENPASAR - Angelista Rofina Kleden; Nyoman Dwika Ayu Amrita; Ni Putu Ayu Suariani; I Komang Dodik Setiawan; Ni Nyoman Puja Narayani; Ni Kadek Ratih Swastini (Universitas Mahendradatta, 2026)
This study aims to explore how consumers in Denpasar develop their behavior when engaging in online shopping. A descriptive qualitative approach was employed through in-depth interviews, observations, and documentation. The findings reveal that online shopping behavior is influenced by several key factors, including trust, perceived risk, satisfaction, generational characteristics, and the features offered by e-commerce platforms. Trust emerges as the most dominant factor, as consumers pay close attention to store reputation, customer reviews, and transaction security. Perceived risk also plays a significant role, particularly concerns about product mismatch or damage during delivery. Consumer satisfaction is formed when the shopping experience meets expectations, which encourages repeat purchases. Furthermore, clear behavioral differences are found among Generations X, Y, and Z, where Generation X tends to be more cautious, Generation Y more adaptive, and Generation Z highly responsive to digital features. Overall, online shopping behavior is shaped by psychological factors, digital experiences, and generational characteristics. These findings are expected to serve as a reference for e-commerce platforms and sellers in improving service quality and digital marketing strategies.